1996
DOI: 10.1002/(sici)1521-186x(1996)17:3<230::aid-bem9>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Human perception of electric fields and ion currents associated with high-voltage DC transmission lines

Abstract: The objective of this study was to assess the ability of humans to detect the presence of DC electric fields and ion currents. An exposure chamber simulating conditions present in the vicinity of high‐voltage DC (HVDC) lines was designed and built for this purpose. In these experiments, the facility was used to expose observers to DC electric fields up to 50 kV/m and ion current densities up to 120 nA/m2. Forty‐eight volunteers (25 women and 23 men) between the ages of 18 and 57 years served as observers. Perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 9 publications
8
37
3
Order By: Relevance
“…Field perception experiments provided evidence that detection thresholds for static EF are much lower for whole-body exposure [29, 31] than limb exposure (e.g., arm and forehand) [30, 34]. Because these effects were confirmed by independent investigators, they can be considered as replicated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Field perception experiments provided evidence that detection thresholds for static EF are much lower for whole-body exposure [29, 31] than limb exposure (e.g., arm and forehand) [30, 34]. Because these effects were confirmed by independent investigators, they can be considered as replicated.…”
Section: Resultsmentioning
confidence: 99%
“…Because these effects were confirmed by independent investigators, they can be considered as replicated. Blondin et al [29] found that under whole-body exposure (static EF strength up to 50 kV/m, 7–11 s/trial) the median detection threshold of seated and grounded male and female subjects was 45.1 kV/m for a static EF. Approximately, 5% of the participants could detect a static EF below 20 kV/m, 33% of the subjects detected a static EF below 40 kV/m and 66% detected fields below 50 kV/m.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At ground level ion currents can lead to charging of objects and thus to undesirable spark discharges and human annoyance [5,6,7]. DC ion currents in AC phases lead to a stronger magnetization of transformers, which manifests itself in higher losses and noise emission [8].…”
Section: Motivationmentioning
confidence: 99%